Integrasi Skema Takaful sebagai Instrumen Perlindungan Objek Pajak Bumi dan Bangunan serta Penguatan Ekonomi Masyarakat di Wilayah Rawan Bencana - Syahrul Sudrajad; Heri Supriyadi; Hendra Prastya (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2025)
Indonesia, as a country with a high level of disaster vulnerability, faces challenges in protecting property assets subject to Land and Building Tax (PBB). This study aims to analyze the concept of integrating the takaful scheme as a protection instrument for PBB objects and its potential for strengthening the economy in disaster-prone communities. The study employed a qualitative approach with descriptive methods through library research. Data were collected from various sources, including books, scientific journals, research reports, laws and regulations, and official documents from relevant institutions. Data analysis employed content analysis techniques with an inductive approach to identify relevant patterns, themes, and concepts. The results indicate that the takaful-PBB integration has a strong sharia foundation based on the principles of ta'awun (concession) and maslahah (benefit), is contextually and operationally feasible, and has the potential to provide multiple positive impacts, including taxpayer financial protection, regional tax revenue stability, and post-disaster economic recovery. The recommended integration model uses a hybrid wakalah-mudharabah scheme with an integrated payment mechanism. Its implementation requires comprehensive regulatory support, commitment from various stakeholders, and a phased strategy tailored to the local context.